A Comparison Study between the Recently Developed Methods of Transportation Problem:A Study on the Lower-Dimensional Problems - Sultana, Nahid; Alam, HS Faruque; Rayb, Ganesh Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2022)
Resource allocation is one of the crucial challenges to the decision-makers. It has a significant impact on the profitability of any company. Freight transport is one type of resource allocation; here the decision-maker has to choose the quantity of products for delivering at a minimum cost from the several plants/factories/sources to the several destinations/ warehouses. We have conducted a comparative study based on secondary data to figure out the best technique for solving the freight transportation problems. Here we have selected 40 balanced and unbalanced problems randomly with dimensions 3×3 to 7×7. We have selected 23 existing methods, some of them are popular and some are recently developed. We compare these 23 methods regarding firstly the optimal solution criterion, and secondly which one can give us the solution in the least step or short time. We have checked the solution at first manually, then by GNU Octave to figure out if there is any inconsistency. Here, the GNU octave is chosen for its easy acceptance and easy input procedure. On our selected problems, the findings show us that the Faster STrongly Polynomial method (FSTP) is best if we consider the least step but concerning the short time MOdifiedDIstribution method worked on Vogel's Approximation Method, well known as VAM-MODI is performing the best. GANIT J. Bangladesh Math. Soc. 42.1 (2022) 035- 049